Insights into the genetic determination of tuber shape and eye depth in potato natural population based on autotetraploid potato genome - Zhao, Long; Zou, Meiling; Deng, Ke; Xia, Chengcai; Jiang, Sirong; Zhang, Chenji; Ma, Yongzhen; Dong, Xiaorui; He, Miaohua; Na, Tiancang; Wang, Jian; Xia, Zhiqiang; et al. (Frontiers in Plant Science, 2023)
Potato is one of the world's most important food crops, with a time-consuming breeding process. In this study, we performed a genome-wide association (GWAS) analysis of the two important traits of potato tuber shape and eye depth, using the tetraploid potato genome (2n=4x=48) as a reference. A total of 370 potatoes were divided into three subgroups based on the principal component analysis and evolutionary tree analysis. The genetic diversity within subgroups is low (5.18×10-5, 4.36×10-5 and 4.24×10-5). Genome-wide linkage disequilibrium (LD) analysis showed that their LD is about 60 Kb. GWAS analysis identified that 146 significant single nucleotide polymorphism (SNP) loci at Chr01A1:34.4435.25 Mb and Chr02A1:28.3528.54 Mb regions are significantly associated with potato tuber shape, and that three candidate genes that might be related to potato tuber traits, PLATZ transcription factor, UTP-glucose-1-phosphate uridylyltransferase and FAR1 DNA-binding domain, are in the association region of Chr02A1. GWAS analysis identified 53 significant SNP loci at Chr05A2:49.64450.146 Mb and Chr06A2:25.86626.384 Mb regions with robust associations with potato tuber eye depth. Hydrolase and methyltransferases are present in the association region of Chr05A2, and three CYPs are present in the association region of Chr06A2. Our findings suggested that these genes are closely associated with potato tuber shape and eye depth. Our study identified molecular markers and candidate genes for improving tetraploid potato tuber shape and eye depth and provided ideas and insights for tetraploid potato breeding.